2015
DOI: 10.1097/bpb.0000000000000184
|View full text |Cite
|
Sign up to set email alerts
|

Does the GMFCS level influence the improvement in knee range of motion after rectus femoris transfer in cerebral palsy?

Abstract: The aim of this study was to evaluate the influence of the Gross Motor Function Classification System (GMFCS) on the outcomes of rectus femoris transfer (RFT) for patients with cerebral palsy and stiff knee gait. We performed a retrospective review of patients seen at our gait laboratory from 1996 to 2013. Inclusion criteria were (i) spastic diplegic cerebral palsy, (ii) GMFCS levels I-III, (iii) reduced peak knee flexion in swing (PKFSw<55°), and (iv) patients who underwent orthopedic surgery with preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Other studies had control groups that were poorly matched 16 . Studies with sizeable, reasonably well‐matched control groups showed effect sizes like those in the original report 17,18 …”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Other studies had control groups that were poorly matched 16 . Studies with sizeable, reasonably well‐matched control groups showed effect sizes like those in the original report 17,18 …”
mentioning
confidence: 75%
“…16 Studies with sizeable, reasonably well-matched control groups showed effect sizes like those in the original report. 17,18 Why have there been so few RCTs examining the outcomes of RFT? The primary answer is that conducting an RCT for surgery in ambulatory children diagnosed with CP is exceptionally difficult due to practical, ethical, and combinatory challenges.…”
mentioning
confidence: 99%
“…A description of each study is presented in Table 1. MINORS score ranged from 4 20 to 21 9 (Supplemental Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…In studies that included a comparison group, results between male and female patients, 92 between participants with diplegia and hemiplegia, 73 between participants with more or less than a 5-degree increase in anterior pelvic tilt, 25 or between patients who received different surgical procedures as part of MLS were compared. 20,30,34,39,54,55,60,86,89 Seventeen studies were prospective cohort studies, of which a singlesubject AB design was used in 1, 22 and 2 surgical procedures as part of MLS were compared in 2. 36,88 Four studies were RCTs in which 2 surgical procedures as part of MLS 32,53 or 2 types of rehabilitation after MLS were compared.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation